A framework for a systems design approach to complex societal problems. (17th January 2019) - da Costa Junior, Jairo; Diehl, Jan Carel; Snelders, Dirk
Abstract : Societal problems concern the complexity of technical, organisational, social, and political issues. The enormous negative impacts of these problems and the inability of problem solvers to deal with high levels of complexity cannot be overcome without a paradigm shift in how we understand and engage with such issues. Two domains have been helpful in bringing about such a shift: Systems Thinking and Design. Although these domains express mutual interest in social–technical systems and complex problem solving, in the literature there are few attempts of bringing the compatibility between them to the attention of designers. This paper aims to contribute to this endeavour by uncovering the role of integrating systems thinking for design, and by providing an overview of the emerging field of systems-oriented design approaches. An extensive literature review outlines significant aspects underlying systems thinking to support its use and further development in design. This paper provides a conceptual framework structured in five clusters: mindset, methodology set, knowledge set, skill set and tool set. The framework is meant to assist designers in integrating systems thinking into design and thereby enable them to better handle complex societal problems.